EFFECTIVENESS CONTENT INSTAGRAM OF @NADI.INDO IN INCREASING BRAND AWARENESS - Putri Wulansari; Qoryna Noer Seyma El Farabi; Wina Puspita Sari; Mentari Anugrah Imsa; Indah Fajar Rosalina (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2025)
This study aims to determine the effectiveness of Instagram content @nadi.indo in increasing brand awareness by using the EPIC Model as a measuring tool to assess the extent to which Instagram content can enhance brand recognition and recall. The research focuses on the Instagram content of the @nadi.indo account managed by Nasari Digital (NADI), targeting active followers of the account as the study population. Employing a quantitative methodology, data were collected through questionnaires distributed to 100 respondents. The EPIC Model, developed by AC Nielsen, was utilized to evaluate four critical dimensions: Empathy, Persuasion, Impact, and Communication. The results revealed an overall average score of 3.385 across these dimensions, indicating that the content falls into the effective category. Specifically, the Persuasion dimension scored the highest at 3.43, demonstrating its strong influence on audience perception. Meanwhile, Empathy, Impact, and Communication scored 3.35, 3.38, and 3.385, respectively, reflecting their moderate yet positive contributions. These findings suggest that the Instagram content successfully fosters brand awareness, though there remains room for improvement to achieve optimal results. The study underscores the importance of maximizing performance in content creation to elevate brand awareness to its highest level, such as Top of Mind recognition. By leveraging the EPIC Model, this research provides actionable insights for digital marketers aiming to enhance brand visibility and engagement on social media platforms like Instagram.